Analisis Peran Pendidikan Informal dalam Pembentukan Karakter Murid Sekolah Dasar - Edi Marta; dian sarmita (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2026)
This study aims to analyze the role of informal education in shaping the character of elementary school students. The study employed a qualitative approach using a library research method. Data sources were obtained from various national scientific journals, books, and relevant articles discussing informal education and character education for elementary school students published between 2019 and 2025. Data collection techniques were carried out through documentation, while data analysis used content analysis through data reduction, data presentation, and conclusion drawing. The results showed that informal education within the family environment has a significant contribution to character building among elementary school students. Character formation is influenced by parental role models, habituation, parenting styles, communication, attention, supervision, and parental involvement in assisting children's development. The dominant character values formed include discipline, responsibility, honesty, self-confidence, cooperation, and social care. In addition, collaboration between families and schools is an important factor in supporting the success of children's character education. This study concludes that informal education within the family needs to be strengthened because it serves as the main foundation in shaping the character of elementary school students to become individuals with good morals and positive social behavior in society.